2020
DOI: 10.3389/fnins.2020.533910
|View full text |Cite
|
Sign up to set email alerts
|

How Do You Feel Now? The Salience Network Functional Connectivity in End-Stage Renal Disease

Abstract: Objective The network connectivity basis of cognitive declines in end-stage renal disease (ESRD) remains unclear. A triple-network model of the salience (SN), executive control, and default mode networks has been suggested to be critical for efficient cognition. Here, we aimed to test the hypothesis that SN may play a role in cognitive impairment in patients with ESRD. Materials and Methods We investigated functional connectivity (FC) alterations within the SN between 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…These alterations were mainly located within DMN, ECN, and ALN. Previous studies have identified impairments in these brain networks [ 10 , 12 , 14 ], which align with the findings of our study. The frontoparietal regions are important components of the DMN and ECN, and the cerebellar-frontoparietal network is involved in various higher cognitive abilities [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These alterations were mainly located within DMN, ECN, and ALN. Previous studies have identified impairments in these brain networks [ 10 , 12 , 14 ], which align with the findings of our study. The frontoparietal regions are important components of the DMN and ECN, and the cerebellar-frontoparietal network is involved in various higher cognitive abilities [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Brain imaging studies demonstrated that functional and structural brain abnormalities in ESRD patients have been detected in several brain regions, including the prefrontal lobe, inferior parietal lobe, cingulate gyrus, precuneus, temporal lobe, hippocampus/parahippocampal gyrus, and insula [ 5–9 ]. There were also abnormalities in the default mode network (DMN) [ 10–12 ], executive control network (ECN) [ 10 , 12 ], sensorimotor network (SMN) [ 12 , 13 ], salience network (SN) [ 10 , 14 ], and affective-limbic network (ALN) [ 15 , 16 ], which are composed of the brain regions mentioned above. The impairment of these brain regions or networks was related to abnormalities in overall cognitive function, working memory, visuospatial/executive function, attention, processing speed, sensorimotor, and emotional processing in ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right anterior insular cortex plays a key role in SN, which serves as a switch between DMN and frontal parietal network (FPN) in cognition control (Joo et al, 2016), is particularly vulnerable to inner environmental change and external insults and significantly correlated with cognitive impairment (Chand et al, 2017;Fathy et al, 2020). And the disruption of SN correlated with cognitive decline in our previous ESRD research (Hu et al, 2020).…”
Section: The Alteration Of Nvc Dysfunction Related Fc In Esrdmentioning
confidence: 75%
“…Moreover, rs-fMRI can detect low-frequency (0.01–0.08 Hz) fluctuations in blood-oxygen-level-dependent (BOLD) signals and can be used to investigate spontaneous neural activity at rest ( Barkhof et al, 2014 ). In hemodialysis patients, impaired functional integrity of extensive brain regions has been measured by using multiple analytical methods based on rs-fMRI, including regional homogeneity (ReHo), amplitude of low frequency fluctuation (ALFF), and functional connectivity (FC) ( Li et al, 2018 ; Chen et al, 2020 ; Hu et al, 2020 ; Guo et al, 2021 ). Although the above results were inconsistent due to the diverse population cohorts and methodologies used, a correlation between functional abnormalities and cognitive dysfunction was indicated.…”
Section: Introductionmentioning
confidence: 99%